Prisoner’s Higher Education in Lithuania and Foreign Countries: Possibilities and Motives - Kvieskienė, Giedrė; Katinaitė - Lodh, Renata (Pedagogika, 2013)
This article presents the educational aspects of prisoner access to higher education while in detention. The theoretical overview discusses the Lithuanian and foreign scientific resources, analyzing the importance of education for all human beings, no matter whether they are incarcerated or not. The empirical part, consists of surveys and questionnaires collected from Ministries of Justice, and other institutions that collect data on prisoners pursuing higher education in seven foreign countries. The empirical evidence highlights the possibilities of and motives for achieving a higher education degree by those performing custodial sentences in prison. The third paragraph of article 24 in Lithuanian law of education No. 38-1804 [11] addresses the right to education for every citizen and legal alien having a permanent or temporary residence in the Republic of Lithuania. The state guarantees the right to primary and secondary education. It also provides for accessibility to higher education, vocational training, and graduate degree programs. The law of education in Article 33, also addresses access to education for socially underprivileged people such as families living in poverty, refugees, people who have dropped out from school at an early age, unemployed, people with addiction problems, as well as those returning from correctional institutions. Thus, despite the social situation in Lithuania, the education system is designed so that it is available to everyone. In order to promote their effective adjustment into the community, disadvantaged individuals need access to education through social services and education assistance programs. This article aims to investigate the opportunities for access to higher education available to prisoners in detention and to understand the motivation. Objective – the availability of higher education in the Lithuanian prison system and the motivation. The article utilizes the following methods: Theoretical: the article reviews the scientific literature and legal analysis of documents of both Lithuanian and foreign authors, sources of information and insight into the normative documents of the formed provisions. Empirical: Surveys conducted with justice ministries or institutions that collect information about higher education for convicts, in seven foreign countries were conducted. Semi-structured interviews with prisoners who have acquired and the benefitted from higher education were also conducted with a written survey. The results of the questionnaire demonstrated that prisoners have a high level of desire to improve themselves through the selection of higher education, while free time is mentioned as a necessary component. Of the surveyed countries, representatives of institutions indicated that prisoners have the opportunity to study in higher education, but this opportunity depends upon certain circumstances. Lithuanian law provides higher education opportunities for socially excluded, at-risk groups. Imprisoned persons have a high level of motivation to be successful in the higher education and for learning. Thus, higher education institutions should have close cooperation with the correctional institutions.